Ijtihad Hukum Kontemporer Melalui Metode Ta‘Līl Maqāshid Ahmad Raisuni - Amin Muhtar (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Islamic law is always required to respond to various life phenomena, so scholars need to design alternative methods to overcome these problems. This study analyzes Ahmad Raisuni's Ijtihad method which uses the maqāsid shari'ah paradigm in the context of contemporary fiqh. The method used is descriptive qualitative with a critical discourse analysis approach. The results of this study indicate that Ahmad Raisuni's Ijtihad method culminates in the ta'līl maqāshidī paradigm, namely the process of tracing the 'illat of law through the maqashid shari'ah framework, where law is understood based on universal values. This ijtihad process can be used to solve practical fiqh problems and decide on the law of new phenomena that do not have a text. There are two steps in applying this method, first, Identifying Legal Problems through Tahqîq al-Manâth, I'tibar al-Maâl, Murâ'ah at-Taghayyurât; second, determining the Priority Scale of Maslahat-Mafsadat by categorizing legal problems into one of the five dharûriyyah maslahat, namely religion, life, descendants, reason, property. The priority scale is determined based on the weight of the dharûriyyah maslahat (Necessities), hâjiyyah (Needs), tahsîniyyah (Luxuries). This method is relevant for new cases, such as in this study, in the case of the Prohibition of Hajj during Covid-19 is legally valid according to sharia law and can even be included in the status of darūrī, and the case of asking for no rain is something that is permissible according to sharia, and can even be sunnah on the same level as the law of asking for rain (istisqā).